FACTORS AFFECTING THE SUSTAINABILITY OF PORANG FARMING BUSINESSES IN PURWOREJO DISTRICT - Ihfaningrum, Aziz; Masyhuri; Suryantini, Any (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
The popularity and existence of porang plants have decreased. The price of porang tubers has decreased drastically. The sustainability of porang farming is influenced by various factors. The purpose of this study was to determine the factors that influence the sustainability of porang farming in Purworejo Regency. The analysis tool used was multiple linear regression with the least squares analysis method or One Least Square (OLS). The results of the study showed that the factors that had a positive effect on the sustainability of porang farming in Purworejo Regency were land area and porang price, while farming experience and farmer age had a negative effect. Keywords: porang, One Least Square (OLS), sustainability